Benign duodenocolic fistula: A case report and review of the literature - Li, Zeyu; Peng, Wenjing; Yao, Hongliang (Frontiers in Surgery, 2023)
Duodenocolic fistula is a rare upper gastrointestinal fistula that can be benign or malignant. However, benign duodenocolic fistulas are particularly rare. Duodenocolic fistulas are often a complication of advanced colon cancer. The most common cause of benign fistulas is perforation of the duodenal ulcer. We report a case of a benign duodenocolic fistula in a patient who presented with abdominal pain, diarrhea, and weight loss. Gastroscopy and an upper gastrointestinal study confirmed the presence of the fistula. Surgery was performed, and the pathological examination demonstrated that the fistula originated from a duodenal ulcer.